Cover Image, Volume 117, Number 7, July 2016. Issue 7 (July 2016) - Al‐Dujaili, Saja A.; Koh, Amy J.; Dang, Ming; Mi, Xue; Chang, Wenhan; Ma, Peter X.; McCauley, Laurie K.
Abstract : Cover : The cover image, by Laurie K. McCauley et al., is based on the Article Calcium Sensing Receptor Function Supports Osteoblast Survival and Acts as a Co‐Factor in PTH Anabolic Actions in Bone, DOI:10.1002/jcb.25447 .